Redesigning the Learning Plan of the English for Islamic Banking Course - Putra, Purnama; Adara, Reza Anggriyashati; Tirtajaya, Mas Deden; Primasari, Winda (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2024)
The development of Islamic Banking both nationally and globally has experienced a significant increase in both the amount of assets managed and their performance. This development is marked by the spread of Islamic banking offices and networks throughout Indonesia. Such development requires the support of human resources who have skills and knowledge related to Sharia-based banking practices as well as able to compete with the global world. In this regard, language skills, especially English language as a global language become important. Nevertheless, there is a dearth in textbooks that specifically teach people how to conduct Sharia banking practices in English. Thus, this research aims to redesign and improve the language skills of employees and prospective employees of Islamic banking through learning plans and learning objectives that suit industry needs. The present study conducted a needs analysis toward employees, lecturers, college alumni, Sharia-based bank guilds. The present study composed a textbook which consists of eight units to teach employees of Sharia-based banks to conduct banking practices in English. The learning materials are also equipped with learning objectives, aiming to improve the language skills of learners.